Evaluating Tennis Player Performance Based on Biomechanical Variables Using Multi Criteria Decision Making Techniques - Qadoori, Rafid Habib; Yas, Qahtan; Ismaeel, Safaa; Qadoori , Majid (Pubmedia Jurnal Pendidikan Olahraga, 2025)
In tennis, choosing the right player can be extremely difficult because their performance in a match depends on many biomechanical criteria. Thus, this study aims to establish a framework to help coaches select the best tennis players based on a set of biomechanical parameters. Tennis involves specific strategies that require players to execute serves accurately and professionally to get more points. Consequently, there are biomechanical criteria that evaluate each player’s performance. Multi-criteria decision-making (MCDM) techniques have provided optimal solutions to various problems. The methodology proposed in this study incorporates several decision-making techniques in two stages: the first involves calculating the weights of the selected criteria by combining triangular fuzzy numbers with the Analytical Hierarchy Process (AHP) technique. The second stage is to select the appropriate alternative using the TOPSIS technique, which focuses on the shortest geometric distance of the alternative from the positive ideal solution and the farthest geometric distance from the negative ideal solution. Additionally, the MOORA technique was applied, based on two attributes: beneficial value and non-beneficial value. The study’s findings indicated that the first attempt (AT-1) was the best alternative in both techniques. Spearman correlation coefficient was employed to assess the relationship between the two techniques, and a sensitivity analysis was conducted based on the ranking results derived from both techniques.